Islamic Values in Banjar Bridal Makeup: Developing Local Wisdom as Character Education - Mutimmatul Faidah; Rizkiani Maulidiyah; Hery Rusmanto (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2021)
Banjar tribe who inhabited Banjarmasin, the capital city of South Kalimantan Indonesia, had a unique bridal makeup. This study aimed to describe the details and the meaning of the makeup, hair styling, clothing, and accessories for Banjar brides. This study was also to describe the Islamic values in the bridal makeup and its potential to be used as character education. This qualitative research used John Fiske's critical ethnographic and semiotic approaches in three areas of study namely signs, codes, and cultures. Data were collected by using interview, observation, and documentation and processed using coding technique. Results showed that Banjar bridal makeup ornaments were in the form of flora, fauna, nature, and geometric. The ornaments described women who were faithful, devout, hardworking, tenacious, patient, humble, and self-respect. Islamic values were manifested in the relationship between humans and God namely faith, Islam, and ihsan (generosity). Human relationship was manifested in a form of social status and kinship. Human-nature relationship was in a form of harmony as well as in a form of noble self-attitude and tough mentality. This make-up could be developed into a media of character education for the bride and groom to create a happily faith-based family.